Leveraging U-Net and selective feature extraction for land cover classification using remote sensing imagery - Leo Thomas Ramos; Angel D. Sappa (Scientific Reports)
Abstract In this study, we explore an enhancement to the U-Net architecture by integrating SK-ResNeXt as the encoder for Land Cover Classification (LCC) tasks using Multispectral Imaging (MSI). SK-ResNeXt introduces cardinality and adaptive kernel sizes, allowing U-Net to better capture multi-scale features and adjust more effectively to variations in spatial resolution, thereby enhancing the model’s ability to segment complex land cover types. We evaluate this approach using the Five-Billion-Pixels dataset, composed of 150 large-scale RGB-NIR images and over 5 billion labeled pixels across 24 categories. The approach achieves notable improvements over the baseline U-Net, with gains of 5.312% in Overall Accuracy (OA) and 8.906% in mean Intersection over Union (mIoU) when using the RGB configuration. With the RG-NIR configuration, these improvements increase to 6.928% in OA and 6.938% in mIoU, while the RGB-NIR configuration yields gains of 5.854% in OA and 7.794% in mIoU. Furthermore, the approach not only outperforms other well-established models such as DeepLabV3, DeepLabV3+, Ma-Net, SegFormer, and PSPNet, particularly with the RGB-NIR configuration, but also surpasses recent state-of-the-art methods. Visual tests confirmed this superiority, showing that the studied approach achieves notable improvements in certain classes, such as lakes, rivers, industrial areas, residential areas, and vegetation, where the other architectures struggled to achieve accurate segmentation. These results demonstrate the potential and capability of the explored approach to effectively handle MSI and enhance LCC results.